Implementation of an mHealth intervention to increase adherence to triage among HPV positive women with HPV-self-collection (ATICA study): post-implementation evaluation from the women's perspective - Kohler, Racquel E. (2023)
Fil: Kohler, Racquel E. Cancer Health Equity, Cancer Institute of New Jersey, Rutgers, The State University of New Jersey; Estados Unidos.